Perception of male and female infant cry aversiveness by adult men. (2nd January 2022) - Richey, Lynnet; Li, Ting; Rilling, James K.
ABSTRACT: Objective : The study aimed to determine why male infants are abused more frequently than female infants. Background : Infant crying is a well-known trigger for Shaken Baby Syndrome or Abusive Head Trauma (SBS/AHT). For unknown reasons, male infants are more often victims of SBS/AHT than female infants. We hypothesised that this sex difference in victimisation was attributable to either acoustic or movement differences between male and female infants when crying, or to gender stereotypes about infant crying (e.g. ' boys don't cry '). Methods : Adult male participants rated auditory and video cry stimuli from male and female infants for aversiveness. Each infant was rated while wearing both blue and pink clothing to denote male or female gender. Results : In two experiments, male infants spent more time producing expiratory phonations than did female infants, and this variable was positively correlated with aversiveness ratings. Including visual stimuli increased male but not female infant cry aversiveness compared with audio stimuli alone. Finally, dressing infants in blue did not increase cry aversiveness. Conclusions : These findings suggest that both the tendency of male infants to produce more expiratory phonations when crying, as well as their visual appearance when crying, may contribute to their increased vulnerability to abuse.